2022
DOI: 10.1128/spectrum.02731-21
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus-Encoded HBsAg Contributes to Hepatocarcinogenesis by Inducing the Oncogenic Long Noncoding RNA LINC00665 through the NF-κB Pathway

Abstract: Hepatitis B virus (HBV) is a major risk factor for hepatocellular carcinoma (HCC). Numerous reports indicate an oncogenic role for HBV-encoded HBsAg; however, the underlying mechanisms are not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…To study the HBV replication cycle, 2.1-and 2.4-kb mRNAs were transcribed from covalently closed circular (ccc) HBV DNA from HepG2.2.15 and NTCP-G2 cells. [34][35][36] A fluorescent probe qPCR kit (Supbio Biotechnology, Guangzhou, China) was used to quantify cellular HBV cccDNA. DNA was extracted using a DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions and denatured at 85°C for 5 min.…”
Section: Quantification Of Covalently Closed Circular Hbv Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…To study the HBV replication cycle, 2.1-and 2.4-kb mRNAs were transcribed from covalently closed circular (ccc) HBV DNA from HepG2.2.15 and NTCP-G2 cells. [34][35][36] A fluorescent probe qPCR kit (Supbio Biotechnology, Guangzhou, China) was used to quantify cellular HBV cccDNA. DNA was extracted using a DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions and denatured at 85°C for 5 min.…”
Section: Quantification Of Covalently Closed Circular Hbv Dnamentioning
confidence: 99%
“…To study the HBV replication cycle, 2.1 and 2.4 kb mRNAs were transcribed from HBV cccDNA. [34][35][36] We analyzed the expression levels of cccDNA in HepG2.2.15 and HepG2-NTCP cells to determine whether the dopamine-mediated downregulation of HBsAg and HBeAg expression was caused by an inhibition of cccDNA formation or transcription. We found that cccDNA formation was unaffected by dopamine when compared to DMSO (Fig.…”
Section: Dopamine Decreased Hbv Hbsag and Hbeag Levels But Not Cccdna...mentioning
confidence: 99%
“…Ahluwalia et al discovered LINC00665 earlier this year to act as a mechanistic tool for HBsAg to induce hepatocarcinogenesis. By stimulating the NF-κB pathway, HBsAg induces LINC00665 levels in hepatocytes, revealing a unique method by which HBV may cause HCC (Ahluwalia et al, 2022).…”
Section: Lncrnas Involved In Hcc Diagnosis and Prognosismentioning
confidence: 99%